DETERMINASI DISIPLIN KERJA, GAJI DAN MOTIVASI TERHADAP KINERJA KARYAWAN KOPERASI BP BATAM - Ratna Dewi; Sri yanti (Universitas Batam, 2017)
Reduced employee performance can change many factors, such as decreased work discipline, unsuitable salaries and motivation that is not managed properly. With the declining performance of employees of agencies / companies will be difficult to achieve organizational goals that have been maintained together the performance of the company will decrease as a whole for it needs the existence of human resource management for the benefit of improving employee performance. Working discipline of well-managed human resources will provide progress for the company and maintain the company's survival, proper remuneration or appropriate salary is also a thing that can arouse employees to excel, and high work motivation will give a good impact for improvement Employee performance to prove the truth of the theory hence this research done by measuring determination of work discipline to employee performance, salary to employee performance, work motivation to employee performance and measure it together to employee performance. The analysis technique is multiple linear regression with quantitative study method using three independent variables, namely work discipline, salary and motivation, which is measured by partial and simultaneous determination and the term of its influence with f test, t test and rank 2. From the results of work discipline study, and significant salary, seen from t test and work discipline, salary and performance motivation are both significantly based on F test and R2 test shows high and positive determination between discipline, salary and motivation on employee performance Kopkar Batam.